Influence of Microstructure on the Properties of a Cold Drawn Alpha-Beth Cu-Zn-Al Alloy - Dewa Nyoman Adnyana (Journal of Mathematical and Fundamental Sciences, 1983)
Abstract. In order to improve its drawability at room temperature, the large strain deformation behavior of a Cu-Zn-Al alloy with a two-phase Î± + Î² structure has been studied. Mechanical tests and quantitative metallography on wire specimens in different stages of the drawing process allowed to come to a better understanding of structure-property relationship. The relative deformation of the two phases has been found to depend on various factors such as the hardness difference between the two phases the drawing strain and the shape indices of the constituents. Sari. Sebuah panduan Cu-Zn-Al dengan struktur a+B, diuji tarik melalui proses "wire drawing" pada temperature kamar. Pengujian ini dimaksudkan untuk mempelajari dan sekaligus memperbaiki sifat "kemampuan tarik" dari panduan. Kawat hasil penatikan dingin ini kemudian diuji mekanik dan kuantitatis metallografi, untuk memperoleh suatu hubungan antara struktur-mikro dan sifat-sifat logam. Hasil penelitian menunjukkan bahwa perbedaan dari sifat deformasi antara fasa a dan fasa B tergantung pada faktor-faktor seperti, perbedaan kekerasan antara kedua fasa, besarnya regangan yang diberikan ketika proses penatikan dingin dan perubahan bentuk butir / struktur dari kedua fasa sebelum dan sesudah penarikan.